Strengthening Digital Literacy for Stakeholders in the Ujung Batu Coastal Area: Penguatan Literasi Digital Bagi Stakeholder di Kawasan Pantai Ujung Batu - Rahayu, Mia; Suni, Muhadjir; Fajar, Andi Muhammad; Zuhud, Muhammad Akbar (Yayasan Ahmar Cendekia Indonesia, 2025)
This community service program aimed to enhance the capacity of local communities in supporting digital-based tourism development. The program adopted a Participatory Action Research (PAR) approach involving 15 stakeholders, including representatives from the tourism office, local beach management, and small business owners. Data were collected through multiple techniques: (a) observation to examine participants’ engagement and skills during training, (b) interviews to explore participants’ responses and reflections on the program’s benefits, and (c) documentation of the promotional content produced by participants. Data were analyzed using thematic analysis to identify patterns of improvement in digital literacy skills. The findings revealed a high level of enthusiasm among participants throughout the sessions, which covered the introduction of digital promotion tools (Google Sites), understanding digital ethics, and practical training in creating promotional content using Canva and CapCut. The main challenge identified was participants’ limited creativity in developing engaging and authentic content. To address this, strategies such as local-based storytelling, the use of user-generated content, and consistent posting schedules were recommended. These strategies not only emphasize technical skills but also foster creative, sustainable, and culturally rooted mindsets. Abstrak Kegiatan pengabdian masyarakat bertujuan meningkatkan kapasitas masyarakat lokal dalam mendukung sektor pariwisata berbasis digital. Kegiatan pengabdian ini menggunakan pendekatan Participatory Action Research (PAR), dengan melibatkan 15 orang peserta dari kalangan stakeholder. Data diperoleh dari berbagai teknik, mencakup: (a) observasi untuk mengamati keterlibatan dan keterampilan peserta selama pelatihan, (b) wawancara untuk menggali respon dan refleksi peserta terhadap manfaat kegiatan, dan (c) dokumentasi hasil konten promosi yang dihasilkan peserta. Data dianalisis dengan teknik analisis tematik untuk mengidentifikasi pola peningkatan kemampuan literasi digital. Hasil pelaksanaan menunjukkan adanya antusiasme tinggi dari peserta terhadap seluruh rangkaian kegiatan, meliputi pengenalan alat promosi digital (Google Sites), pemahaman etika digital, serta praktik pembuatan konten promosi menggunakan aplikasi Canva dan CapCut. Tantangan utama yang diidentifikasi adalah keterbatasan kreativitas peserta dalam mengembangkan konten yang menarik dan autentik. Oleh karena itu. strategi berbasis storytelling lokal, pemanfaatan konten wisatawan, serta penerapan konsistensi unggahan disarankan sebagai solusi. Strategi ini tidak hanya menekankan aspek teknis, tetapi juga menumbuhkan pola pikir kreatif, berkelanjutan, dan berorientasi pada nilai budaya lokal.